2017
DOI: 10.1093/aob/mcw265
|View full text |Cite
|
Sign up to set email alerts
|

You are what you get from your fungi: nitrogen stable isotope patterns in Epipactis species

Abstract: As hypothesized, it is suggested that the observed gradient in 15 N enrichment of Epipactis species is strongly driven by 15 N abundance of their mycorrhizal fungi; i.e. ɛ 15 N in Epipactis spp. associated with rhizoctonias < ɛ 15 N in Epipactis spp. with ectomycorrhizal basidiomycetes < ɛ 15 N in Epipactis spp. with ectomycorrhizal ascomycetes and basidiomycetes < ɛ 15 N in Epipactis spp. with ectomycorrhizal ascomycetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 59 publications
9
61
0
Order By: Relevance
“…The two investigated species display different nutritional modes: E. helleborine is a partially heterotrophic (mixotrophic) orchid species (Bidartondo et al, ; Schiebold, Bidartondo, Karasch, Gravendeel, & Gebauer, ) that obtains a part of its carbon from its own photosynthesis and the other part from its mycorrhizal fungi. In this species, the fungus may provide 20%–100% of its carbon to the plant, depending on the time in the growth season (Gonneau et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The two investigated species display different nutritional modes: E. helleborine is a partially heterotrophic (mixotrophic) orchid species (Bidartondo et al, ; Schiebold, Bidartondo, Karasch, Gravendeel, & Gebauer, ) that obtains a part of its carbon from its own photosynthesis and the other part from its mycorrhizal fungi. In this species, the fungus may provide 20%–100% of its carbon to the plant, depending on the time in the growth season (Gonneau et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses have revealed that partial mycoheterotrophy may be more widespread than previously assumed, as plants that were initially assumed to be autotrophic based on their 13 C signature appeared to be significantly enriched in isotopes other than 13 C (Gebauer et al, ). Using normalized enrichment factors, Schiebold, Bidartondo, Karasch, Gravendeel, and Gebauer (), for example, showed that in a large number of terrestrial orchids of the genus Epipactis , normalized enrichment factors for 15 N showed a continuous gradient from low values (<5) in so‐called ‘rhizoctonia’ orchids ( Epipactis palustris and E. gigantea ) (Figure ) to high values for species that are assumed to form orchid mycorrhizas exclusively with ectomycorrhizal ascomycetes ( E. neglecta , E. muelleri , E. leptochila and E. distans ). Similarly, normalized enrichment factors for 13 C continuously increased from zero to five (Figure ).…”
Section: Trophic Modes: a Continuum From Autotrophy To Mycoheterotrophy?mentioning
confidence: 99%
“…The green box represents the mean enrichment factors (± 1 SD ) for autotrophic reference plants that were sampled together with the Epipactis species. The red box represents mean enrichment factors (± 1 SD ) of all partially mycoheterotrophic orchid species that associate with ectomycorrhizal fungi that were reviewed by Hynson, Madsen, et al () before the publication of Schiebold et al (). (Figure reproduced from Schiebold et al, , with permission)…”
Section: Trophic Modes: a Continuum From Autotrophy To Mycoheterotrophy?mentioning
confidence: 99%
“…The G. repens tendency to enrichment in δ 15 N compared to EcM plants is very important for this element is currently presumed to be very important in the displaying of partial heterotrophy (Schiebold et al 2017).…”
mentioning
confidence: 99%
“…The mechanism of 15 N increase in IMHOs is still unclear too (Hynson et al 2013), but for the mixotrophic genus Epipactis 15 N enrichment in plant is strongly driven by 15 N abundance of their mycobionts (Schiebold et al 2017). δ 15 N values for G. repens were rather variable, but their similarity to those for litter saprotrophic fungi was detected (Table 4).…”
mentioning
confidence: 99%